Shoot Heterogeneity Effects on Shiraz/Richter 99 Grapevines. II. Physiological Activity - Cloete, H.; Archer, E.; Novello, V.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2016)
In this study, the physiology of normally developed and underdeveloped shoots is compared in an attempt to quantify the effect of shoot heterogeneity in a Shiraz/Richter 99 vineyard, located in the Stellenbosch area of the Western Cape, South Africa. Comparisons are made between normally developed and underdeveloped shoots from shaded and well-exposed canopies. In the first five weeks after véraison, photosynthetic and transpiration rates, stomatal conductance and water-use efficiency (WUE) decreased as berry ripening progressed, while the internal CO2 levels of the leaves increased. Since differences in activity between individual leaves from normally developed and underdeveloped shoots only became apparent in the third week after véraison, it seemed as if the leaf area per shoot played a more important role than the photosynthetic output per unit leaf area in determining photosynthetate supply to the rest of the vine up to this stage. From the third week after véraison, higher levels of photosynthetates were produced by normally developed shoots than by underdeveloped shoots, due to the larger effective leaf area per shoot as well as the higher photosynthetic activity per unit leaf area. This points to premature senescence of the leaves on underdeveloped shoots. The quantity and quality of the yield from normally developed shoots are expected to benefit from the higher physiological output of the leaves. The enhancing effect on leaf functioning induced by canopy exposure became apparent from the third week after véraison.